Analisis Strategi Pemasaran Dilakukan Untuk Meningkatkan Volume Penjualan Makaroni Di Bisnis Fabek Snack - Andrianto; Ahmad Syahbani; , Enggar Budi Pratama; Fathur Rohman; Kanzul Fikri; Sri Lestari (Jurnal Hilirisasi Pengabdian Masyarakat, 2024)
This research aims to analyze the marketing strategy implemented by "Fabek Snack" in an effort to increase sales of their Macaroni products. The approach used is descriptive qualitative by taking types and sources of data from primary data and secondary data. The analytical method applied is descriptive analysis with a focus on the Marketing Mix concept and SWOT analysis.The main data was obtained through direct observation of the marketing practices of "Fabek Snack" and interviews with related parties, while secondary data was obtained from related literature and internal company documentation. Descriptive analysis was carried out to provide an in-depth picture of the marketing strategy implemented.The analysis results show that "Fabek Snack" has succeeded in implementing a comprehensive marketing strategy using the Marketing Mix concept, namely product, price, promotion and location. In addition, SWOT analysis helps identify strengths, weaknesses, opportunities and threats that influence the marketing of "Fabek Snack" Macaroni products.In an effort to increase sales, the company has focused on strengthening internal strengths, minimizing weaknesses, exploiting market opportunities, and overcoming potential threats. The implementation of this strategy provides in-depth insight into how "Fabek Snack" successfully manages and markets their Macaroni products, thereby making a positive contribution to the company's marketing success.